PERAN KOMUNITAS OMAH DHUAFA DALAM PEMBERDAYAAN ANAK JALANAN DI KABUPATEN GRESIK - Novi Khusni Purwa Daini; Lukman Arif (Halu Oleo University, 2023)
The issue of street children is a social problem that is constantly developing. Street children arise because of marginalization and polarization, which if left unchecked can lead to social inequality in society. The increase in street children in Gresik Regency shows that the government has not fully overcome this problem. For this reason, these social issues need to be resolved together. The existence of civil society is an alternative to intervene in alleviating the problem of street children. One of them is the existence of a Non-Govenmental Organization in Gresik Regency, namely the Omah Dhuafa Community which seeks to realize the welfare of street children through empowerment activities. This study aims to find out about the role of the Omah Dhuafa Community in providing empowerment to street children in Gresik Regency. The research method used is qualitative, where data collection is obtained through interviews, observation and documentation. Based on the results of the research and discussion, shows that the homeless community has carried out its role well, even though there are limitations in providing empowerment for street children, such as limitations in collaborating with the government, as well as limitations in providing training to street children.